Diliman network simulation II - De Jesus, Anthony M. (2004)
ATM (asynchronous transfer mode) networks operate under a dedicated-connection switching technology that organizes digital data into cell units and transmits them over a physical medium utilizing digital signal technology. Networks as such are used in interconnecting organizations and units spanning a large area. An example of an ATM network is the UP Diliman Network (DILNET), DILNET is a 155 Mbps ATM network linking thirty-four (34) buildings inherent in the UP Diliman campus. Changes in the topology of the DILNET have been made in the span of a year since it was last studied as an undergraduate project during the second semester of A.Y. 2002-03. The main objective of this project is to simulate the current DILNET using the NS2 simulator application and to examine if the bandwidth is still adequate to service the demand of the network. Supplementary to this is the analysis of the effect of the changes made to the topology to the network traffic. The graphs to be derived from the data gathered will then be analyzed as part of the correlation analysis and will be also compared to the results from the previous project. Analysis of the effect of voice-over-IP (VoIP) on the traffic will also be considered. Futhermore, a mechanism for maintaining the Quality of Service (QoS) for VoIP in the DILNET will be proposed. The mechanism will be tested using test scenarios that will be developed.